Ginger, Honey, And Lemon Aromateraphy As A Complimentary Teraphy For First Trimester Morning Sickness - Sari, Lutfiana Puspita; Nurrasyidah, Rahmi (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
Morning sickness affects 70-85% of pregnant women during the first trimester. Lemon aromatherapy, combined with ginger’s anti-inflammatory properties and the chemoreceptor-inhibiting effects of honey and pyridoxine, may help reduce nausea by modulating serotonin, dopamine, and histamine activity in the vomiting center. This study aims to assess the effectiveness of ginger, honey, and lemon aromatherapy as a complementary therapy for alleviating morning sickness symptoms. This pre-experimental study involved 60 pregnant women experiencing morning sickness, selected through incidental sampling. Data collection, conducted from May to August 2024, utilized the PUQE-24 score. Univariate analysis was used for frequency distributions, while bivariate analysis employed a paired t-test to assess pre- and post-intervention differences. An independent two-sample t-test determined differences between groups. Lemon aromatherapy, ginger, and honey significantly reduced nausea before and after the intervention (p 0.000). The use of ginger, honey, and lemon aromatherapy resulted in a significant difference in mean PUQE scores (p 0.000). Aromatherapy with ginger, honey, and lemon is useful in lowering the Intense vomiting in pregnant women throughout the first trimester. Keywords: Aromateraphy, Ginger, Honey, Lemon, Morning Sickness